2012
DOI: 10.3892/ijo.2012.1447
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of interleukin-6 receptor suppresses the proliferation of H460 lung cancer stem cells

Abstract: Abstract. IL-6/6R signaling is closely associated with tumor growth and poor prognosis. Although there is evidence that interleukin-6 receptor (IL-6R)-mediated signaling promotes the growth and malignancy of cancer, the role of IL-6R in cancer stem cells (CSCs) is poorly defined. This study investigated the role of IL-6R in the proliferation of CSCs. Sphere-forming cells were isolated from the H460 non-small cell lung cancer (NSCLC) cell line and identified as CSCs using confocal microscopy, RT-PCR and WST-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Also, the IL-6 levels in serum were investigated in patients with lung cancer before and during radiotherapy (RT). They found that IL-6 levels were higher compared to controls and were further elevated during RT [40][41][42][43]. In addition, IL-1β and IL-8 both are known to promote tumour progression through regulating tumour growth and invasion [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the IL-6 levels in serum were investigated in patients with lung cancer before and during radiotherapy (RT). They found that IL-6 levels were higher compared to controls and were further elevated during RT [40][41][42][43]. In addition, IL-1β and IL-8 both are known to promote tumour progression through regulating tumour growth and invasion [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that IL-6 may be important in lung cancer stem cells, as opposed to the bulk tumor cells. 32 Beyond direct targeting of tumor cells, targeting IL-6-related inflammation may have beneficial effects on patient quality of life through improvement in cachexia and lung cancer-related anemia. 33 In conclusion, our results and those of others suggest that further study of IL-6 targeting with siltuximab should be considered in human clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating IL-6 level is also a prognostic marker for survival in advanced NSCLC patients or those treated with chemotherapy [15]. Targeting IL-6 signaling via blocking the IL-6R and IL-6 with siRNA or mAbs resulted in reduced H460 cell (a cell line of human NSCLC) proliferation [16]. On the other hand, human lung adenocarcinomas cells can produce their own IL-6 to promote cell proliferation [17].…”
Section: Introductionmentioning
confidence: 99%